Exercise-induced expression of monocarboxylate transporter 2 in the cerebellum and its contribution to motor performance. (28th October 2016) - Hoshino, Daisuke; Setogawa, Susumu; Kitaoka, Yu; Masuda, Hiroyuki; Tamura, Yuki; Hatta, Hideo; Yanagihara, Dai
Highlights: Inhibition of lactate transport via MCT2 in the cerebellum impaired motor performance. Acute exercise increased MCT2 expression in the cerebellum at the transcriptional level, but not at the protein level. These results suggest that lactate transport via MCT2 in the cerebellum may play an important role in motor performance. Abstract: Monocarboxylate transporter 2 (MCT2) is an important component of the lactate transport system in neurons of the adult brain. Purkinje cells in the cerebellum have been shown to have high levels of MCT2, suggesting that this protein has a key function in energy metabolism and neuronal activities in these cells. However, it is not known whether inhibition of lactate transport via MCT2 in the cerebellum affects motor performance. To address this question, we examined motor performance in mice following the inhibition of lactate transport via MCT2 in the cerebellum using α-cyano-4-hydroxycinnamate (4-CIN). 4-CIN or saline was injected into the subarachnoidal space of the cerebellum of mice and motor performance was analyzed by a rotarod test both before and after injection. 4-CIN injection reduced retention time in the rotarod test by approximately 80% at 1 h post-injection compared with pre-injection. No effect was observed at 2 h post-injection or in mice treated with the vehicle control. Because we observed that MCT2 plays an important role in motor performance, we next investigated the effects of acute exercise on MCT2 transcription and protein levels in mice sampled pre-exercise and at 0 and 5 h after 2 h of treadmill running. We found a significant increase in MCT2 mRNA levels, but not of protein levels, in the cerebellum at 5 h after exercise. Our results indicate that lactate transport via MCT2 in the cerebellum may play an important role in motor performance and that exercise can increase MCT2 expression at the transcriptional level.